An Interview With David Peterson and David Jones: Envisioning the Future of Rural Healthcare - Peterson, David; Jones, David (Maine Policy Review, 1996)
Managed care and other healthcare changes may impact Maine differently than more urban states. Managed care companies, striving to create economies of scale in healthcare financing, often prefer to fold rural regions into larger plans that emanate from more populous hubs. In much of Maine, many question whether this will be best for the consumers and providers of rural healthcare. Maine Policy Review interviewed David Peterson, president and chief executive officer of The Aroostook Medical Center (TAMC), and family practitioner David Jones who practices at Aroostook Family Practice and is an active member of TAMC’s medical staff, to obtain their views on rural healthcare and the impact of state and national healthcare trends on rural providers.